Factors Associated With Dropout Between Bacille Calmette Guerin (BCG) and Measles Vaccination in A Village Development Committee of A District - Basel, P L; Shrestha, L B (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: The Expanded Programme on Immunization is one of the first priorities of the Government of Nepal. The high national dropout rate (11.3%) demonstrates that immunization opportunities are lost as approximately one of every nine children in contact with immunization services are slipping â€œout of the systemâ€ before the age of 12 months. This study is an attempt to explore the situation of the enhancing factors for dropout. Objectives: The main objective of the study was to identify the reasons of dropout between BCG and Measles vaccination in Kapan Village Development Committee (VDC) of Kathmandu district. Methods: This was a descriptive study. of children ranging from 12 to 23 months of age residing in Kapan VDC. (N=81) mothers were interviewed to obtain the information.Â Results: The study revealed that Magar/Gurung in the area were found to dropout more (78.6%). Female children were more likely to dropout than male children. About 70% of children dropout were from labor class, and/or illiterate families. Majority of the mothers (42.5 %) said that the child was ill so they did not go for routine vaccination. However, 50.7% of dropout children received quality care. These findings were corroborated with the findings of key informant interview. Conclusions: The major reason of dropout of measles vaccine was found to be the perceived contraindication regarding the immunization. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords:<span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> BCG versus Measles, Dropout, Immunization<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>